The Effect of Organic Fertilizer and Liquid Complementary Fertilizer on The Seed Growing Medium from Topsoil - Fazlul Wahyudi; Bambang J. Priatmadi; Joko Purnomo (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2021)
In coal mine reclamation activities, topsoil is generally used as the top layer on the reclamation land surface and the primary material in the growing medium for reclamation plant seeds due to its abundant availability. Topsoil generally has a low fertility rate because the soil layers between horizons have been mixed. Improvement of topsoil quality can be performed by adding organic fertilizers. This study aimed to identify the effect of organic fertilizers, liquid complementary fertilizers (LCF), and their interactions on selected soil's chemical properties from the topsoil used as a seed growing medium. This study used a factorial completely randomized design (CRD) with two factors, consisting of organic fertilizer factors (guano phosphate, Subur Ijo, vermicompost) and LCF factors (IMO, liquid smoke, Vermiwash). The results showed that the independent treatment of organic fertilizers and LCF had a very significant effect on pH. The independent treatment of organic fertilizers had a very significant effect on organic C and Total K. Meanwhile, the interaction between the two treatments had a very significant effect on the Total N and Total P of the growing media. The addition of organic fertilizers and LCF can improve topsoil quality to be used as a medium for growing media.